A pharmacokinetic–pharmacodynamic model for the MET tyrosine kinase inhibitor, savolitinib, to explore target inhibition requirements for anti‐tumour activity. (7th December 2020) - Jones, Rhys D.O.; Grondine, Mike; Borodovsky, Alexandra; San Martin, Maryann; DuPont, Michelle; D'Cruz, Celina; Schuller, Alwin; Henry, Ryan; Barry, Evan; Castriotta, Lillian; Anjum, Rana; Petersson, Klas; et al.
Abstract : Background and Purpose: Savolitinib (AZD6094, HMPL‐504, volitinib) is an oral, potent, and highly MET receptor TK inhibitor. This series of studies aimed to develop a pharmacokinetic–pharmacodynamic (PK/PD) model to link inhibition of MET phosphorylation (pMET) by savolitinib with anti‐tumour activity. Experimental Approach: Cell line‐derived xenograft (CDX) experiments using human lung cancer (EBC‐1) and gastric cancer (MKN‐45) cells were conducted in athymic nude mice using a variety of doses and schedules of savolitinib. Tumour pMET changes and growth inhibition were calculated after 28 days. Population PK/PD techniques were used to construct a PK/PD model for savolitinib. Key Results: Savolitinib showed dose‐ and dose frequency‐dependent anti‐tumour activity in the CDX models, with more frequent, lower dosing schedules (e.g., twice daily) being more effective than intermittent, higher dosing schedules (e.g., 4 days on/3 days off or 2 days on/5 days off). There was a clear exposure–response relationship, with maximal suppression of pMET of >90%. Data from additional CDX and patient‐derived xenograft (PDX) models overlapped, allowing calculation of a single EC50 of 0.38 ng·ml −1 . Tumour growth modelling demonstrated that prolonged, high levels of pMET inhibition (>90%) were required for tumour stasis and regression in the models. Conclusion and Implications: High and persistent levels of MET inhibition by savolitinib were needed for optimal monotherapy anti‐tumour activity in preclinical models. The modelling framework developed here can be used to translate tumour growth inhibition from the mouse to human and thus guide choice of clinical dose and schedule.